2005
DOI: 10.1007/s10903-005-1389-6
|View full text |Cite
|
Sign up to set email alerts
|

Welfare and Immigration Reform and Use of Prenatal Care Among Women of Mexican Ethnicity in San Diego, California

Abstract: Foreign-born women and, in particular, Hispanic foreign-born women, are less likely to have insurance, are less likely to have insurance that covers prenatal care, and are less likely to utilize prenatal care compared with US-born Hispanic women. Significant concern has been raised regarding the ability of immigrant women to access prenatal care services because of severe restrictions imposed on immigrants' eligibility for Medicaid-funded services following the passage in 1996 of the federal Personal Responsib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
3

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 20 publications
0
15
0
3
Order By: Relevance
“…One record was included through citation searching. A final 46 articles were included in the narrative synthesis,21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, 50, 51, 52, 53, 54, 55, 56, 57, 58, 59, 60, 61, 62, 63, 64, 65, 66 of which two reported on the same study,48, 58 and 19 qualified for meta-analysis22, 25, 29, 30, 34, 35, 36, 37, 41, 45, 47, 48, 49, 50, 51, 53, 60, 62, 65 (figure 1; table 1; appendix). All included studies were done in high-income contexts, and examined the health-related impact of entry (eight studies)32, 35, 47, 48, 53, 57, 58, 59, 61 and integration (37 studies)21, 22, 23, 24, 25, 26, 27, 28,…”
Section: Resultsmentioning
confidence: 99%
“…One record was included through citation searching. A final 46 articles were included in the narrative synthesis,21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, 50, 51, 52, 53, 54, 55, 56, 57, 58, 59, 60, 61, 62, 63, 64, 65, 66 of which two reported on the same study,48, 58 and 19 qualified for meta-analysis22, 25, 29, 30, 34, 35, 36, 37, 41, 45, 47, 48, 49, 50, 51, 53, 60, 62, 65 (figure 1; table 1; appendix). All included studies were done in high-income contexts, and examined the health-related impact of entry (eight studies)32, 35, 47, 48, 53, 57, 58, 59, 61 and integration (37 studies)21, 22, 23, 24, 25, 26, 27, 28,…”
Section: Resultsmentioning
confidence: 99%
“…Lack of employment, health insurance, and low income are the most prevalent barriers to health care for undocumented immigrant women. These barriers and their effects are exacerbated by language barriers, unfamiliarity with the health care system, as well as fear of being arrested and deported (Asch, Leake, Anderson, & Gelberg, 1998;Asch, Leake, & Gelberg, 1994;Guendelman, Chavez, & Christianson, 1994;Kullgren;Loue, Cooper, & Lloyd, 2005). According to Gabrielle Lessard, staff attorney at the National Immigration Law Center (NILC) in Los Angeles, the consequences related to immigration status include complications from untreated diseases such as asthma, diabetes, hypertension, vision problems and cancers, among others, for children and adults (Iqbal, 2004).…”
Section: Resultsmentioning
confidence: 99%
“…[18][19][20] In addition, the unauthorized sometimes fear that use of healthcare services will prevent future legalization because they are "likely to become a public charge," although federal regulations have exempted medical services from this use in immigration application denials. 15 Loue et al 21 detect fear by the unauthorized that they will be turned away for services, whereas Hagan et al 18 identify hostile relationships with some providers (but see Loue et al, 21 who found that measurable fear is not correlated with lower use of healthcare services by 6 FAMILY & COMMUNITY HEALTH/JANUARY-MARCH 2009 immigrants). Beyond the healthcare system itself, there is fear of arrest while traveling to access healthcare services.…”
Section: Literature Reviewmentioning
confidence: 99%